Development and analysis of the loading characteristic of accumulate fuel injection system Common Rail of the engine 50 RT-flex - Polovinka, Edward; Tabulinsky, Igor (Technology audit and production reserves, 2023)
The object of research are hydrodynamical processes in fuel delivery system of marine diesel engine of type RT-flex with accumulate fuel injection system of type Common Rail. The problem, being solved, is maintenance of an effective operation of the specified diesel engines due to perfection work of their fuel equipment. The results of simulation modeling of the injection process by accumulator fuel delivery system Common Rail of the 50RT-flex engine are presented. On the basis of the functional diagram of system, a calculation model has been compiled that provides a description of the operation of the systems main blocks. The load characteristic of the fuel equipment is built in the traditional version – the dependence of the fuel delivery parameters from the engine load at a constant speed. For the system under consideration, the control element is the valve assembly connecting the injection control unit (ICU) with injectors. The parameters of the load characteristic in this study are modes with a constant engine speed n=124 rpm and a change in the opening angle of the control valve in the range – jv=6.6–14.4 °CA. The parameters of the devices that largely determine the characteristics of the fuel delivery and the quality of the working processes of a diesel engine are considered in more details. Such an element of the system is ICU, the working body of which is the dosing piston. The main parameters of its operation when delivering fuel are the magnitude and speed of the stroke. For the load characteristics in the accepted range of the valve control valve opening angle jv from 6.6 to 14.4 °CA (2.18 times), the piston stroke was hp=4.29–8.61 mm (2.0 more). In this case, the dependence of hp on jv is linear. Area of use of the data received during research, ship crews and the shore services providing operation of vessels are. A material is applied in process of high school and is already used in various educational forms. The given researches are useful to developers and builders of marine diesel engines of a considered class.